Analytical progress and challenges for the detection of oxygenated polycyclic aromatic hydrocarbon transformation products in aqueous and soil environmental matrices: A review. Issue 5 (4th March 2019) - Pulleyblank, Coren; Cipullo, Sabrina; Campo, Pablo; Kelleher, Brian; Coulon, Frederic
Abstract: Over the past 20 years, a growing body of research has raised concerns about the toxicity, fate, and transport of oxygenated transformation products of polycyclic aromatic hydrocarbons. Research targeting these diverse compounds in soil and water systems has been challenged by a lack of standard analytical techniques and suitable reference materials. However, recent efforts towards the consolidation of traditional analytical techniques as well as the development of novel approaches to improve sample preparation and hyphenated instrumental techniques show promise. This review discusses progress and challenges for both trends in analytical method development and makes recommendations for supporting oxygenated PAH research.